2016
DOI: 10.1016/j.chemphys.2016.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Fast solute diffusivity in ionic liquids with silyl or siloxane groups studied by the transient grating method

Abstract: To achieve ionic liquids (ILs) that show fast solute diffusivity independent of viscosity domination, sixteen ILs containing Si or Si-O-Si groups (SiILs) were synthesized. Diffusion coefficients of three solute molecules with different molecular sizes, i.e., CO, diphenylacetylene, and diphenylcyclopropenone, were determined in SiILs using the transient grating method and the results were compared to other solvent system. SiILs showed distinguishably faster diffusivity for the smallest solute, CO, than conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…found that, at 295 K, the silyl‐based [Si−C 1 ‐mim][NTf 2 ] IL has higher density (1.43 g cm −3 ) than that of siloxane‐based [(SiOSi)−C1‐mim][NTf 2 ] IL (1.32 g cm −3 ). Comparing the results reported by Endo et al . for [Si−C 3 ‐mim][NTf 2 ] IL at 295 K (1.317 g cm −3 ) and those measured in this work at 293 (1.319 g cm −3 ) and 298 K (1.315 g cm −3 ) for [Si−C 1 −C 3 mim][NTf 2 ] indicates that the additional methyl group in the side chain of [Si−C 1 −C 3 mim][NTf 2 ] does not significantly affect IL density.…”
Section: Resultssupporting
confidence: 83%
“…found that, at 295 K, the silyl‐based [Si−C 1 ‐mim][NTf 2 ] IL has higher density (1.43 g cm −3 ) than that of siloxane‐based [(SiOSi)−C1‐mim][NTf 2 ] IL (1.32 g cm −3 ). Comparing the results reported by Endo et al . for [Si−C 3 ‐mim][NTf 2 ] IL at 295 K (1.317 g cm −3 ) and those measured in this work at 293 (1.319 g cm −3 ) and 298 K (1.315 g cm −3 ) for [Si−C 1 −C 3 mim][NTf 2 ] indicates that the additional methyl group in the side chain of [Si−C 1 −C 3 mim][NTf 2 ] does not significantly affect IL density.…”
Section: Resultssupporting
confidence: 83%
“…Second, they exhibit rapid solute diffusivity and enhanced ionic conductivity. [117,118] Third, ILs are suitable for the functionalization of both micro-and macrosiloxane molecules. [119][120][121][122] Micromolecular siloxane and cyclic oligosiloxane-based ILs can exhibit fluidity at low temperature, quite compatible with current liquid electrolytes.…”
Section: Ils Functionalized Organosilicon Electrolytesmentioning
confidence: 99%
“…In particular, Endo and co-workers reported the translational diffusion of solutes in viscoelastic solvents including ionic liquids and silicone oils. 37 Compared to solvents of similar viscosities, the deviation from the SE relation was especially large in silicone oils. The viscoelastic relaxation of silicone oil is slow as we have demonstrated in our previous work.…”
Section: Resultsmentioning
confidence: 99%
“…There have been many studies on the translational diffusion of small solute molecules, where large deviation from the hydrodynamic SE model was reported. In particular, Endo and co-workers reported the translational diffusion of solutes in viscoelastic solvents including ionic liquids and silicone oils . Compared to solvents of similar viscosities, the deviation from the SE relation was especially large in silicone oils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation